The stars down to earth : and other essays on the irrational in culture - Adorno, Theodor W. (Routledge, 1994)
The Stars Down to Earth shows us a stunningly prescient Adorno. Haunted by the ugly side of American culture industries he used the different angles provided by each of these three essays to showcase the dangers inherent in modern obsessions with consumption. He engages with some of his most enduring themes in this seminal collection, focusing on the irrational in mass culture - from astrology to new age cults, from anti-semitism to the power of neo-fascist propaganda. He points out that the modern state and market forces serve the interest of capital in its basic form. Stephan Crook's introduction grounds Adorno's arguments firmly in the present where extreme religious and political organizations are commonplace - so commonplace in fact that often we deem them unworthy of our attention. Half a century ago Theodore Adorno not only recognised the dangers, but proclaimed them loudly. We did not listen then. Maybe it is not too late to listen now.